Genetic Association and Expression of Myoglobin Gene Related to Mineral Content in IPB-D2 Chickens - P. Liong; A. K. Alfiah; I. Khaerunnisa; S. Darwati; R. Afnan; A. B. Dharmayanthi; M. F. Al-Habib; C. Sumantri (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
Myoglobin (MB) gene encodes the protein of myoglobin, which is a protein found in muscle tissues that plays a crucial role in binding and storing oxygen. This study aimed to analyze the polymorphism of the MB gene, examine its relationship with the meat mineral content, and analyze its expression in the liver and thigh muscle tissue of IPB-D2 chicken. A total of 55 IPB-D2 chickens were used in this study. Identification of the gene polymorphism, quantification of the mineral content, and gene expression were performed using the direct sequencing method, the Atomic Absorption Spectroscopy (AAS) method, and the qRT-PCR, respectively. Chicken thigh muscle and liver tissues were used as the source of mRNA in this study. The statistical analysis methods used were the chi-square test to test Hardy-Weinberg equilibrium, and the T-test for mineral association analysis and gene expression analysis. IPB-D2 chicken on average contains 17.81, 0.22, 16.50, and 0.34 mg/kg of Fe, Se, Zn, and Mn, respectively. Two SNPs were found in 5’UTR of the MB gene, namely SNP g.17 G>T and SNP g.25 T>C. Genotype TT (g.17 G>T) and genotype CC (g.25 T>C) were significantly (P<0.05) associated with high Fe content in IPB-D2 chicken. The gene expression analysis showed that MB mRNA expression in the liver was not statistically different between high Fe (TT/CC) and low Fe (GG/TT and GT/TC) genotype combination. Meanwhile, in the thigh muscle, MB mRNA expression in TT/CC genotype combination was significantly higher than GG/TT and GT/TC genotype combination (P<0.05). These results suggest that the identified polymorphisms in the IPB-D2 MB gene could serve as references for investigating similar gene in other chicken breeds, especially regarding Fe, Se, Zn, and Mn mineral content.